PENGARUH MOTIVASI KERJA, LINGKUNGAN KERJA DAN KESEJAHTERAAN TERHADAP KINERJA GURU SMP SWASTA - Untung Sriwidodo, Kartono & (Universitas Slamet Riyadi, 2009)
Abstract The purpuse of the research were (1) to examine and analyse the significance of working motivation influence, working environment and the welfare toward private school teachersâ€™ working parcially in Tegowanu District Grobogan Regency (2) to examine and analiyse the sicnificance of working motivation influence, the working enfironment, and the welfare equally towardâ€™ private school teachers working in Tegowanu District Grobogan Regency (3) to know the dominant influence among working motivation, working, environment and welfare towardâ€™ private school teachers working in Tegowanu District Grobogan Regency.The research population were all private school teachers in Tegowanu Dustrict Grobogan Regency. The total of private schools were 3 schools and the total of teachers were 50 teachers. The conclusion of the research were (1) the hypothesis which stated â€there is a significance working motivation toward the private school teachersâ€™ working in Tegowanu District Grobogan Regencyâ€ was correct (2) the hypothesis which stated â€there is a significance influence in working, environment toward the private school teachersâ€™ working in Tegowanu District Grobogan Regencyâ€ was correct (3) the hypothesis which stated â€therer is a significance in welfare toward the private school teachersâ€™ working in Tegowanu District Grobogan Regencyâ€ was correct (4) the hypothesis which stated â€there is a significance in working motivation, working environment and welfare toward private school teachers working in Tegowanu District Grogogan Regencyâ€ was crrect (5) the hypothesis which stated â€the welfare is more influence then the working motivation and, working environment toward the private school teachers working in Tegowanu District Grobogan Regencyâ€ was crrrct. Keywords: Motivation, Environment, welfore and working